Measurement of thrombopoietic activity through the quantification of megakaryocytes in bone marrow cytology and reticulated platelets - Silva, L. F. N. [UNESP]; Golim, M. A. [UNESP]; Takahira, Regina Kiomi [UNESP] (Elsevier B.V., 2012)
Reticulated platelets are considered as marker for bone marrow thrombopoiesis. The aim of the study was evaluate the role of reticulated platelets as markers of thrombopoiesis in dogs. Reticulated platelets analysis by flow cytometry and megakaryocyte quantification by bone marrow cytology were determined ill 29 healthy adult dogs (control group), 14 dogs with thrombocytopenia without megakaryocytic hypoplasia (group A) and 14 dogs with thrombocytopenia which presented megakaryocytic hypoplasia (group B), detected by bone marrow aspiration cytology. Blood samples were collected and the platelet rich plasma was obtained for reticulated platelets quantification in flow cytometry. Megakaryocytes were quantified in aspiration cytology by two techniques in marrow particles, and correlated to reticulated platelets counts. There are no differences between megakaryocyte quantification. Although there is no correlation between reticulated platelet values and megakaryocyte in bone marrow cytology, the interpretation of reticulated platelet values can be based both on absolute or relative corrected values. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Reticulated platelets; Megakaryocytes; Dog; Bone marrow; Flow cytometry